Technology status tracing and trends in construction robotics: a patent analysis - Liu, Yuming; Alias, Aidi Hizami bin; Haron, Nuzul Azam; Bakar, Nabilah Abu; Wang, Hao (Elsevier, 2024)
The advent of construction robotics (CR) has been rendered technically and economically viable by the proliferation of microprocessors and a decline in costs. A captivating epoch in CR has emerged, and it defies conventional interpretation. We ask how to extract the frontier research topics from patents, which countries are driving innovation in CR, and what policies are contributing to the current situation. This paper uses patent analysis and text mining to study 1831 C R-related patents and finds four clusters from the Derwent Innovations (DI) database. The patent remaining life impact (PRLI) index is calculated. The results show an increase in the number of CR-related patents annually. China leads in the number of patent publications, while the US and other patent organizations have played critical roles in the field. An improved technology evolutionary path tracing visualization identifies several hotspots. Additionally, the policy strategy matrix (PSM) analyzes the industrial stimulation policies of the two countries with the most considerable proportion, providing an explanation for predicting future technology research and development (R&D) and the direction of optimization.